2022
DOI: 10.1371/journal.pone.0267052
|View full text |Cite
|
Sign up to set email alerts
|

To what extent do callers follow the advice given by a non-emergency medical helpline (NHS 111): A retrospective cohort study

Abstract: National Health Service (NHS) 111 helpline was set up to improve access to urgent care in England, efficiency and cost-effectiveness of first-contact health services. Following trusted, authoritative advice is crucial for improved clinical outcomes. We examine patient and call-related characteristics associated with compliance with advice given in NHS 111 calls. The importance of health interactions that are not face-to-face has recently been highlighted by COVID-19 pandemic. In this retrospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Where contact was made with another service after the index call, this was most commonly presentation at an ED, which occurred in around 7% of cases and is similar to other studies using linked data (Lewis et al, 2021; Nakubulwa et al, 2022). Over 10% of these attendances were classed as non-urgent, i.e.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Where contact was made with another service after the index call, this was most commonly presentation at an ED, which occurred in around 7% of cases and is similar to other studies using linked data (Lewis et al, 2021; Nakubulwa et al, 2022). Over 10% of these attendances were classed as non-urgent, i.e.…”
Section: Discussionsupporting
confidence: 83%
“…However, despite this, the rate of contact with primary care services was higher in this study than has been reported elsewhere. For example, Nakubulwa et al (2022) linked 111 call data with primary and secondary services in London between 2013– 2017 and reported only 35% of callers triaged to a primary care disposition had contact with a GP. In contrast, experimental statistics from NHS Digital suggest that patients in the Bradford area were less likely to attend a planned GP appointment than elsewhere in England in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes these services are used to provide a prescription to consumers where appropriate [10]. Telephone advice and triage lines are generally staffed by non-clinicians (or a mix of clinical and non-clinical staff) and rely upon data input to help guide decision making [12,13]. Advice provided in the latter is more generalised in nature and aimed to equip consumers with enough information to self-manage their care (when appropriate) or seek out appropriate avenues for further assessment and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the model was informed by relevant stakeholders and a linked dataset. However, it is nevertheless a simple working model, and does not take account of factors that have previously been associated with inappropriate ED attendance, such as age, sex, ethnicity and clinical input into the 111 call 6…”
Section: Discussionmentioning
confidence: 99%
“…Other studies examining caller behaviour and the impacts on the wider healthcare system5 6 have used datasets from 2017 and earlier, and patterns of activity identified then, may not be applicable now.…”
Section: Introductionmentioning
confidence: 99%